BISPHOSPHONATE RELATED OSTEONECROSIS OF THE JAWS - Shah, SAA; Aslam, A; Mirza, AI; Ali, S (Journal of Ayub Medical College Abbottabad, 2010)
Bisphosphonates are used widely for a variety of bone conditions, most notably intravenous bisphosphonate in the treatment of metastatic bone lesions and multiple myeloma and oral bisphosphonates for osteoporosis. Recently, a peculiar form of osteonecrosis limited to the jaws has been discovered especially with the use of intravenous bisphosphonates. We review briefly the mechanism of action of these drugs, the clinical features and staging of the disease, prevention strategies and management options. Keyword: BRONJ, Multiple myeloma, Hyperbaric oxygen